COMPARATIVE STUDY OF REGISTRATION MATERIALS FOR DETERMINATION OF INTERMAXILLARY RELATIONSHIP IN THE POSITION OF MAXIMUM INTERCUSPATION - Hlushko, T.R.; Vovk, Yu.V.; Vovk, V.Yu. (World of Medicine and Biology, 2019)
In modern dental prosthetic practice, there often occur inconsistencies of occlusion in oral cavity and on cast dental models, leading to search for a solution to the problem of improving the registration accuracy of occlusal relationships of dentitions. The purpose of the work was clinical laboratory study of bite registration materials selected efficiency. Examination of 10 patients was conducted. Registration biomaterials: Consiflex, Аluwaх, Futar D were successively placed on occlusal surfaces of each patient. After polymerization of registration materials, determination of biometric deviation of markers from complementary position in the regions of dentitions under study was performed. Clinical and laboratory research with the use of Futar D registration materials in patients with intact dentitions demonstrated lower optimum of differences between BDM indices, indicating a better complementarity during recording the maximum intercuspation of this material in comparison with Consiflex and metalized wax.
Keywords: bite registration material; maximum intercuspation registration; intact dentitions